Analysis of interactions between glucan, water dikinase and either isoamylase or starch branching enzymes in detrmination of starch structure - Adegbaju, Muyiwa Seyi (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.